Daya Dukung Padang Lamun Di Kawasan Wisata Pulau Pari, Kepulauan Seribu - Christon Christon; Noverita Dian Takarina; Hayati Sari Hasibuan (Bumi Lestari Journal of Environment, 2018)
This research was conducted using carrying capacity analysis method. The purpose of this research was to analyze the seagrass condition and the carrying capacity of seagrass tourism development in Pari Island. Quantitative method is used to reach the research purpose. The result showed that seagrass species found were Halodule ophalis, Cymodocea rottundata, Enhalus acoroides, dan Thalassia hemprichii. Seagrass’ coverage and density at Bintang Beach were recorded as 59.83% and 76 ind/m2 respectively, 47.56% and 54 ind/m2 at Kresek Beach, and 16.61% and 9 ind/m2 at Pasir Perawan Beach. Diversity index of seagrass in Pari Island was 1,199, categorized as moderate condition. The carrying capacity score for seagrass as tourism object in Pari Island in ecological aspect were 94 tourists/day for Bintang Beach, 59 tourists/day for Kresek Beach, and 58 tourists/day for Pasir Perawan Beach. Based on social aspect, local people of Pari Island were mostly welcome the tourists, and the tourists were quite not satisfied with the tourism objects. In economic aspect, tourism activities increase local peoples’ income.